INTERVAL PARAMETER’S IDENTIFICATION OF THE LINEAR DYNAMIC SYSTEM ON THE BASIS OF INTERVAL DATA - Dyvak, Mykola; Stakchiv, Petro; Kalishchuk, Iryna (International Journal of Computing, 2014)
The task of interval parameter’s identification of linear dynamic system is considered. Possibility of application of calculation procedures of parameter’s interval identification of the static system for the decision of this task is shown. The method of parameter’s set identification of the linear dynamic system in form of multidimensional ellipsoids is proposed.